2014
DOI: 10.1038/cmi.2014.74
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CD8+CD57+ T cells in patients with acute myocardial infarction

Abstract: Although T cells are known to be involved in the pathogenesis of coronary artery disease, it is unclear which subpopulation of T cells contributes to pathogenesis in acute myocardial infarction (MI). We studied the immunological characteristics and clinical impact of CD8 1 CD57 1 T cells in acute MI patients. The frequency of CD57 1 cells among CD8 1 T cells was examined in peripheral blood sampled the morning after acute MI events. Interestingly, the frequency of CD57 1 cells in the CD8 1 T-cell population co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 34 publications
(41 reference statements)
1
35
0
Order By: Relevance
“…CD57 ? senescent T cells has been correlated with poor outcome after acute myocardial infarction [78]. Moreover, several studies have reported that in patients with acute coronary syndrome, statins, which are HMG-CoA reductase inhibitors, decrease the frequency of circulating CD4 ?…”
Section: Senescent T Cells In Atherosclerosis and Coronary Artery Dismentioning
confidence: 99%
“…CD57 ? senescent T cells has been correlated with poor outcome after acute myocardial infarction [78]. Moreover, several studies have reported that in patients with acute coronary syndrome, statins, which are HMG-CoA reductase inhibitors, decrease the frequency of circulating CD4 ?…”
Section: Senescent T Cells In Atherosclerosis and Coronary Artery Dismentioning
confidence: 99%
“…CMV is associated to the expansion of CD8+ CD57+ T cells [8,9] that have independently been related to coronary artery disease [57]. In addition, high frequencies of these cells are associated with short-term mortality in patients with acute myocardial infarctions [58].…”
Section: Immunosenescence CMV and Cardiovascular Diseasementioning
confidence: 99%
“…CD57 seems to play various roles in differentiation of the neural crest and lymphocytes (see the “Introduction”). In the same context, the antibody is available as a marker of inactive or senescent T lymphocytes [ 14 ] as well as of specific lymphocytes involved in the initial stage of atherosclerosis [ 15 16 ] and myocardial infarction [ 17 ]. Unfortunately, we failed CD8 immunostaining of the present materials (see the final sentence of “Materials and Methods”).…”
Section: Discussionmentioning
confidence: 99%